Penguatan Kompetensi Mahasiswa Pendidikan Vokasi Melalui Integerasi Kurikulum Berbasis Industri Di Era Digital - Riza Hasan; Deni Deni (VOCATECH: Vocational Education and Technology Journal, 2026)
AbstractThis study aims to conceptually analyze the role of industry-based curriculum integration in strengthening vocational students’ competencies and its implications for graduates’ work readiness in the digital era. This study employs a qualitative approach using a narrative literature review method, focusing on the conceptual synthesis of relevant literature without strictly following systematic review procedures. The review is based on various studies examining the relationship between vocational education, industry demands, and competency development in the digital context. The findings indicate that industry-based curriculum integration through a work-based learning approach plays a significant role in enhancing students’ competencies, including technical skills, soft skills, and digital literacy. These competencies serve as key factors in improving employability, which significantly influences graduates’ work readiness. This study also proposes an integrative conceptual model demonstrating that the relationship between industry-based curriculum integration and graduates’ work readiness is mediated by the strengthening of student competencies. The findings provide practical implications for developing more adaptive and industry-relevant vocational curricula in response to the demands of the digital era.     AbstrakPenelitian ini bertujuan untuk menganalisis secara konseptual peran integrasi kurikulum berbasis industri dalam penguatan kompetensi mahasiswa pendidikan vokasi serta implikasinya terhadap kesiapan kerja lulusan di era digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode narrative literature review yang berfokus pada sintesis konseptual terhadap literatur relevan tanpa mengikuti prosedur systematic review secara ketat. Kajian ini didasarkan pada berbagai literatur yang membahas keterkaitan antara pendidikan vokasi, kebutuhan industri, dan pengembangan kompetensi di era digital. Hasil kajian menunjukkan bahwa integrasi kurikulum berbasis industri melalui pendekatan work-based learning berperan signifikan dalam penguatan kompetensi mahasiswa yang mencakup kompetensi teknis, soft skills, dan literasi digital. Penguatan kompetensi tersebut menjadi faktor kunci dalam meningkatkan employability yang berdampak signifikan terhadap kesiapan kerja lulusan pendidikan vokasi. Penelitian ini secara konseptual menghasilkan model integratif yang menunjukkan bahwa hubungan antara integrasi kurikulum berbasis industri dan kesiapan kerja lulusan dimediasi oleh penguatan kompetensi mahasiswa. Temuan ini memberikan implikasi praktis bagi pengembangan kurikulum pendidikan vokasi yang lebih adaptif dan relevan dengan kebutuhan industri di era digital